Ascending aortic cannulation in acute type A aortic dissection: a frightening but lifesaving procedure - Yalcin, Mihriban; Godekmerdan, Eda; Tayfur, Kaptan Derya; Urkmez, Melih; Yazman, Serkan (The European Research Journal, 2016)
Different cannulation sites (e.g., femoral artery, axillary artery, left ventricular apex, and ascending aorta) and perfusion techniques (anterograde or retrograde) have been used for treating acute type A aortic dissection. The patient’s pathology and status determine the cannulation site. We present our experience with ascending aortic cannulation for acute type A aortic dissection.